Effect of types of natural food and their combination on growth dab survival rate Of tambaqui (Colossoma macropomum) larvae - Dede Novendra; Hamdan Alawi; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The effect of types of natural food and their combinations on growth and survival rate of tambaqui (Collossoma macropomum) larvae was conducted at the Fish Hatchery and Breeding Lalboratory, Faculty of Fisheries and Marine Sciences, University of Riau in 18-L recirculating water system aquaria for 6 weeks rearing period. Six-days old larvae were stocked at density of 30 larvae/ aquarium and fed with Artemia nauplii for 6 weeks (treatment 1), water fleas 6 weeks (Treatment 2); tubifex worm 6 weeks (Treatment 3); Artemia nauplii 3 weeks followed by tubifex worm 3 weeks (treatment 4); water fleas 3 weeks followed by tubifex worm 3 weeks (Treatment 5) and Artemia nauplii 2 weeks, followed by water fleas 2 weeks and lasted by tubifex worm 2 weeks (Treatment 6). The weight gain (2.2 g) and specific growth rate (9.75%/day) were significantly higher for larvae fed with tubifex worm for 6 weeks than those fed with artemia and water flea or their combinations. Therefore, the survival rate of larvae was best (74.4%) when fed with either artemia nauplii followed by tubifex worm or water flea followed by tubifex worm.Key words: Natural food, artemia nauplii, water flea, tubifex worm, collossoma macropomum larvae